1) Answer: The part of the quadratic formula tells us whether the quadratic equation can be solved by factoring is b^2-4ac
2) 4x^2+6x+2=0
ax^2+bx+c=0; a=4, b=6, c=2
b^2-4ac=(6)^2-4(4)(2)=36-32
b^2-4ac=4
Answer: b^2-4ac=4
<span>This must be your answer:
Expanded: 1/5 x 10x + 1/5 x -25 </span>
Answer:
$2x
Step-by-step explanation:
- x × 2 = 2x
I hope this helps!
Answer: True
Step-by-Step Explanation:
=> 2x + 3y = -7 (Eq. 1)
=> -x = 2y (Eq. 2)
=> x = 1, y = -3
Substitute values of ‘x’ and ‘y’ in Eq. 1 :-
=> 2x + 3y = -7
= 2(1) + 3(-3) = -7
= 2 + -9 = -7
=> -7 = -7
=> LHS = RHS
Therefore, it is a Solution.
Answer:
Step-by-step explanation:
1.44x2.2=3.168 pounds